An interacting two-fluid scenario for dark energy in anisotropic cosmological model - Singh T.; Chaubey R. (My University, 2025)
The open anisotropic cosmological model of the early Universe is considered. We study the evolution of the dark energy parameter within anisotropic Bianchi type-V cosmological model filled with barotropic fluid and dark energy. The solutions have been obtained for power law and exponential forms of the expansion parameter. (They correspond to constant deceleration parameter in general relativity.) For large time (i.e., t → ∞), the models tend asymptotically to an isotropic Friedmann-Robertson-Walker cosmological model under certain conditions. © 2013 Published by NRC Research Press.